2020
DOI: 10.3389/fcimb.2020.00389
|View full text |Cite
|
Sign up to set email alerts
|

Does the Oral Microbiome Play a Role in Hypertensive Pregnancies?

Abstract: Chronic hypertension during gestation is associated with an increased risk of adverse pregnancy outcomes including pre-eclampsia, fetal growth restriction and preterm birth. Research into new chemotherapeutic regimes for the treatment of hypertension in pregnancy is limited due to concerns about fetal toxicity and teratogenicity, and new therapeutic avenues are being sought in alternative physiological pathways. Historically, generation of the vasodilator nitric oxide was believed to be solely from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 79 publications
0
7
0
1
Order By: Relevance
“…Interestingly, the potential role of oral microbiota dysbiosis in the pathogenesis of pregnancy hypertension and its complications has been suggested [ 31 ]. In a study by Pralhad et al, involving 200 pregnant women, the influence of periodontitis on the risk of pregnancy hypertension was analyzed.…”
Section: Periodontitis and The Risk Of Arterial Hypertensionmentioning
confidence: 99%
“…Interestingly, the potential role of oral microbiota dysbiosis in the pathogenesis of pregnancy hypertension and its complications has been suggested [ 31 ]. In a study by Pralhad et al, involving 200 pregnant women, the influence of periodontitis on the risk of pregnancy hypertension was analyzed.…”
Section: Periodontitis and The Risk Of Arterial Hypertensionmentioning
confidence: 99%
“…Moreover, high estrogen levels promote infection by Candida (Kumar et al, 2013;Fujiwara et al, 2017). Willmott and co-workers (2020) demonstrated that the composition of the oral microbiome accurately reflects the dietary content of nitrate and the healthy regulation of blood pressure (Willmott et al, 2020). Bacteria in the oral cavity, located primarily on the tongue's surface, reduce nitrate enzymatically, resulting in the presence of nitrite in the saliva, which is subsequently transformed in the stomach into nitric acid and then reduced to nitric oxide (NO).…”
Section: The Oral Microbiomementioning
confidence: 99%
“…Bacteria in the oral cavity, located primarily on the tongue’s surface, reduce nitrate enzymatically, resulting in the presence of nitrite in the saliva, which is subsequently transformed in the stomach into nitric acid and then reduced to nitric oxide (NO). This process is related to blood pressure in two different ways: the plasma level of nitrate is related inversely to blood pressure, and, at the same time, NO is a key signal molecule in connection with processes that regulate the circulatory system ( Willmott et al., 2020 ).…”
Section: Changes In Microbiome Associated With Pregnancymentioning
confidence: 99%
See 2 more Smart Citations